A Critical Review on the Book A Realist Theory of Science - Maryam Poostforush; Mostafa Taqavi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Different narratives have been offered so far of the nature of science and scientific activity. Roy Bhaskar as one of the leading critical realists seeks to set the ground for a Copernican Revolution in the philosophy of science which seems to have been handled well by him. To this end, he proceeds    to highlight the ontological debates and at the same time pays attention to the social nature of science. In A Realist Theory of Science, which contains original and powerful arguments in the philosophy of science, not only does he raise criticisms against some philosophical schools and explains his own theory of science, rather he does also broach significant categories in the philosophy of science. His remarks with their philosophical basis can inspire the scholar who studies Bhaskar’s philosophy. Among the most important ones of these categories, one can refer to the mutuality of ontological realism and epistemological relativism as well as his criticism of Tarsky’s theory of truth. This essay aims at reviewing Bhaskar’s key work in the philosophy of natural sciences and identification of its points of weakness and strength using a descriptive ـ analytic method. This is undertaken through a detailed review of the whole book in view of its formal, qualitative, and content dimensions. The essay is concluded by a number of practical suggestions.